If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 6y = 56 Solving -2x + 6y = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. -2x + 6y + -6y = 56 + -6y Combine like terms: 6y + -6y = 0 -2x + 0 = 56 + -6y -2x = 56 + -6y Divide each side by '-2'. x = -28 + 3y Simplifying x = -28 + 3y
| 3(x-4)=24 | | -1+42-36=13x | | 6x+-7y=-91 | | 3x^2-5x+16=0 | | 6t-9-3t=4 | | .2x+12=-.25x | | 7x^2+10=-2 | | 2x-7=6x+25 | | 1+3x-1+16=x+2+4x | | 4r+5r-6r=21 | | 2x-3y=21 | | -1-7x+42-6=36 | | 7x-2y=2 | | x^3+2x^2+6x+12= | | -8k+7k=2k-12 | | 4(x-3)+5(2-3x)=9 | | 3m+20=8m-5 | | 3n-5=-48-40n | | (2c+1)(c+3)=0 | | 7y+y=7y+ny | | 2x-x=8-x | | x^2+30x+114=0 | | 3n-5=48-4n | | 2/5(10x-25)=14 | | -4(3-2-6)= | | 6y^2+13y+5=0 | | 3(5+x)=5(7-(-2)) | | x(x+1)-10(x+1)= | | 6x-6=9x-9 | | -4a+7=8-5a | | 2u(3u^2+-1)-(-8U^3+-14u+6)= | | 2u(3u^2-1)-(-8U^3-14u+6)= |